Tissue-resident, memory CD8+ T cells are effective in clearing intestinal Eimeria falciformis reinfection in mice - Shi, Fangyun; Zhang, Sixin; Zhang, Ning; Yu, Ying; Sun, Pei; Tang, Xinming; Liu, Xianyong; Suo, Xun (Frontiers in Immunology, 2023)
Eimeria, a cousin of malarial parasites, causes coccidiosis that results in huge losses in the poultry industry. Although live coccidiosis vaccines have been developed and used widely for the successful control of the disease, the mechanism underlying protective immunity remains largely unknown. Using Eimeria falciformis as a model parasite, we observed that tissue-resident memory CD8+ T (Trm) cells accumulated in cecal lamina propria following E. falciformis infection in mice, especially after reinfection. In convalescent mice challenged with a second infection, E. falciformis burden diminished within 48-72 h. Deep-sequencing revealed that CD8+ Trm cells were characterized by rapid up-regulation of effector genes encoding pro-inflammatory cytokines and cytotoxic effector molecules. While FTY720 (Fingolimod) treatment prevented the trafficking of CD8+ T cells in peripheral circulation and exacerbated primary E. falciformis infection, such treatment had no impact on the expansion of CD8+ Trm cells in convalescent mice receiving secondary infection. Adoptive transfer of cecal CD8+ Trm cells conferred immune protection in naïve mice, indicating that these cells provide direct and effective protection against infection. Overall, our findings not only explain a protective mechanism of live oocyst-based anti-Eimeria vaccines but also provide a valuable correlate for assessing vaccines against other protozoan diseases.